Pengaruh Kebijakan Ekonomi terhadap Akses Layanan Kesehatan di Indonesia: Studi Kasus Kebijakan Fiskal, Moneter, dan Sosial dalam Mengatasi Ketimpangan antara Daerah Perkotaan dan Pedesaan - I Dewa Ayu Nyoman Utari Sastrani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study examines the influence of economic policies on access to healthcare services in Indonesia, with particular attention to fiscal, monetary, and social policies amid persistent disparities between urban and rural areas. Despite the implementation of various economic measures, including the National Health Insurance program (JKN), unequal distribution of health facilities and economic instability remain major challenges in achieving equitable healthcare access. The study aims to analyze how economic policies shape healthcare accessibility and to identify key constraints affecting service equity. A qualitative research approach was employed through in-depth interviews with government officials, healthcare workers, and community members, complemented by policy document analysis related to health financing and social protection. The data were analyzed thematically to capture patterns in policy implementation and its impacts on healthcare access. The findings indicate that while JKN has expanded population coverage, disparities in service quality and facility availability persist, particularly in remote and rural regions. In addition, uneven fiscal allocation and macroeconomic pressures such as inflation and interest rate fluctuations reduce household purchasing power and limit effective utilization of healthcare services. The study concludes that more inclusive and regionally balanced economic policies are essential to strengthen healthcare infrastructure, improve service quality, and ensure equitable access to healthcare across Indonesia.